Observed Versus Expected COVID-19 Infections Among National Football League Players During the 2020 Season. Issue 2 (March 2022) - Lopez, Michael J.; Mack, Christina; Bliss, Thompson; Wasserman, Erin B.; Myers, Emily; Solomon, Gary; Lynch, John; Casolaro, Anthony; Osterholm, Michael; Hanfling, Dan; Mayer, Thom; Sills, Allen K.
Abstract : Background: The National Football League (NFL) and National Football League Players Association implemented a set of strict protocols for the 2020 season with the intent to mitigate COVID-19 risk among players and staff. In that timeframe, the league's 32 teams completed 256 regular season games and several thousand meetings and practices. In parallel, community cases of COVID-19 were highly prevalent. We assess the risk of holding a 2020 NFL season by comparing community and player COVID-19 infections. Methods: We used county-level COVID-19 test data from each team to establish baseline distributions of infection rates expected to occur in a population similar in age and sex to NFL players. We used a binomial distribution to simulate expected infections in each community cohort and compared these findings with observed COVID-19 infections in players. Results: Over a 5-month period (1 August 2020 to 2 January 2021), positive NFL player infections (n = 256) were 55.7% lower than expected when compared with simulations from NFL community cohorts. For 30 of 32 teams (94%), observed counts fell at or below expectation, including 28 teams (88%) for which rates were lower. Two teams fell above baseline expectation. Conclusions: The NFL/NFLPA protocols that governed team facilities, travel, gameday, and activities outside of the workplace were associated with lower infection rates among NFL players compared with the surrounding community. The NFL's 2020–2021 season are consistent with the hypothesis that robust testing and behavioral protocols support a safe return to sport and work. Abstract : Supplemental Digital Content is available in the text.